BIOSTRATIGRAPHY AND STRUCTURE OF THE UPPER QUATERNARY DEPOSITS AND SOME PALEOGEOGRAPHIC FEATURES OF THE NORTH CASPIAN REGION - Bezrodnykh Yu.P.; Romanyuk B.F.; Deliya S.V.; Magomedov R.D.; Sorokin V.M.; Parunin O.B.; Babak E.V. (My University, 2004)
Among materials of the OJSC Lukoil obtained in the northern Caspian region, there are cores samples recovered from the depth of 7 to 37 m below bottom, piston cores, and high-resolution seismic profiles. These materials are used to measure 14C age of sediments and to study biostratigraphy and structure of the Upper Quaternary deposits and paleogeography of the region. Mollusks, benthic foraminifers, diatoms, spores and pollen from sediments recovered by a series of boreholes characterize in detail and substantiate the discrimination and correlation of the Novocaspian, Mangyshlak, upper and lower Khvalynian, Atel', and upper Khazarian beds. The 14C dates indicate that the beds accumulated in the time intervals of 0-7000, 7000-9000, 9000-16000, 17000-30000, and >30000 years, respectively. Lithologic and seismoacoustic data suggest four large sea-level drops relative to the current level in the time spans of the Mangyshlak (-40 to -50 m), Enotaevsk (-20 m), Atel' (-70 m), and the Chernyi Yar-Astrakhan' (or Intra-Khazarian) regressions (-90 m). The events are recognizable based on deep incision channels of the Paleovolga and on lacustrine deltaic and continental facies.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная